한반도 동해남부연안에 자생하는 말잘피, 게바다말의 생장 특성 - 박정임; 김재훈; 김종협; 김명숙; PARK, JUNG-IM; KIM, JAE HOON; KIM, JONG-HYEOB; KIM, MYUNG SOOK (Pada (Hanʼguk Haeyang Hakhoe), 2019)
The surfgrass Phyllospadix japonicus is a dominant seagrass species playing critical ecological roles on the eastern coast of Korea. However, few studies have been conducted on the ecological characteristics of this species, generally due to the turbulent water conditions in its habitat. In this study, to examine the growth dynamics of P. japonicus, we investigated monthly changes in morphological characteristics, density, biomass, and leaf productivity as well as changes in the underwater irradiance, water temperature, and water column nutrient concentrations of its habitat from August 2017 to July 2018. Underwater irradiance and water temperature showed clear seasonal changes increasing in spring and summer and decreasing in fall and winter. Nutrient availability fluctuated substantially, but did not display any distinct seasonal trend. Morphological characteristics, shoot density, biomass, and leaf productivities of P. japonicus exhibited significant seasonal variations, increasing in spring and decreasing in fall months. Spadix of P. japonicus occurred from March to August, with the maximum spadix percentage(15.8%) occurred in May 2018. The average leaf productivity of P. japonicus per shoot and area were 2.1 mg sht-1 d-1 and 7.5 g m-2 d-1, respectively. The optimum water temperature for the growth of P. japonicus in this study was between 13-14℃. The productivity of P. japonicus was not correlated with underwater irradiance, water temperature and nutrient concentrations. These results suggest that the study site provide sufficient amount of underwater irradiance, suitable water temperature range and nutrients for the growth of P. japonicus. 말잘피 게바다말은 우리나라 동해안의 암반조하대에 우점하는 잘피로, 이 곳 연안생태계에서 중요한 기능을 수행한다. 그러나 심한 파도에 노출된 거친 생육 환경으로 인해 지금까지 게바다말의 생태 자료는 미비한 실정이다. 본 조사에서는 동해남부해역에 서식하는 게바다말의 생태적 특성을 알아보기 위해 2017년 8월부터 2018년 7월까지 게바다말 군락지의 환경과 게바다말의 형태적 특성, 밀도, 생체량과 잎 생산성의 변화를 조사하였다. 수중광량과 수온은 봄과 여름에 증가하고 가을과 겨울에 감소하는 뚜렷한 계절 경향을 보였다. 해수의 영양염 농도는 조사 시기마다 유의한 차이를 보였으나, 뚜렷한 계절 변동은 나타나지 않았다. 게바다말의 형태, 밀도, 생체량과 잎 생산성도 가을에 감소하고 봄에 증가하였다. 게바다말의 육수화서는 2월 이후 나타났고, 5월에 최대 비율(15.8%)을 보인 후 8월 이후 탈락되었다. 게바다말의 개체당 및 단위면적당 평균 잎 생산성은 각각 2.1 mg sht-1 d-1과 7.5 g m-2 d-1이었다. 게바다말의 생장이 가장 활발한 수온은 13-14℃로 조사되었다. 게바다말의 잎 생산성은 수중광량, 수온, 영양염 농도와 유의한 상관관계가 나타나지 않았다. 이는 이 지역이 게바다말 생장에 필요한 충분한 빛, 적절한 수온 범위와 영양염 농도를 제공함을 의미한다.